2018
DOI: 10.3390/app8020194
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Nitrate Removal from Water Using a Submerged Membrane Adsorption Hybrid System with Four Adsorbents

Abstract: Excessive concentrations of nitrate in ground water are known to cause human health hazards. A submerged membrane adsorption hybrid system that includes a microfilter membrane and four different adsorbents (Dowex 21K XLT ion exchange resin (Dowex), Fe-coated Dowex, amine-grafted (AG) corn cob and AG coconut copra) operated at four different fluxes was used to continuously remove nitrate. The experimental data obtained in this study was simulated mathematically with a homogeneous surface diffusion model that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…Large fitted k f values for μGFH might be due to its higher adsorption loading towards As(V) than μTMF. These findings are consistent with previous studies, 59 in which larger k f values for adsorbents were achieved with higher adsorbent capacity, during adsorption of nitrate onto commercially available and laboratory‐prepared anion exchange resins in an adsorption–membrane hybrid process. A higher mass transfer at the external surface of the material provides a higher degree of adsorption for the target pollutant.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Large fitted k f values for μGFH might be due to its higher adsorption loading towards As(V) than μTMF. These findings are consistent with previous studies, 59 in which larger k f values for adsorbents were achieved with higher adsorbent capacity, during adsorption of nitrate onto commercially available and laboratory‐prepared anion exchange resins in an adsorption–membrane hybrid process. A higher mass transfer at the external surface of the material provides a higher degree of adsorption for the target pollutant.…”
Section: Resultssupporting
confidence: 93%
“…A mathematical model incorporating the HSDM has been applied to describe the concentration profiles of arsenic adsorption systems, 8,58–61 These studies have demonstrated that the HSDM allows the simulation of the dynamic behavior of a variety of adsorbates (phosphate, arsenic, chloroform and vanadium) onto porous adsorbents (e.g. activated carbon, GFH and μGFH), as long as the mass transfer from the solution to the adsorption sites within the adsorbent particles is constrained by mass transfer resistances such as surface diffusion and external film mass transfer, as depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Low-pressure membrane processes, such as microfiltration or even ultrafiltration, have a reasonable energy demand and produce superior quality treated water with a rather controllable fouling of membranes and incurring quite low capital and operational costs [27]. The low-pressure membrane processes are not able to remove monoand polyvalent ions, i.e., arsenic species, from water sources, although they can efficiently remove suspended solids, colloids, bacteria, viruses and micro-particles [28]. If the cost-effective small sized GFH adsorbent (having a substantially lower commercial price of only 1.6 €/kg on a dry basis) has the potential to remove arsenic species from drinking water sources, it might then be employed in the adsorption-microfiltration (MF) hybrid treatment scheme to economically and efficiently remove arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…El agua se desplaza a través de fangos activados en donde se evidencia la separación de las partículas sólidas. Este reactor puede operar con altas concentraciones de sólidos suspendidos [62]. Además, cuenta con dos unidades de purificación.…”
Section: Reactor Mbrunclassified